1982
DOI: 10.1073/pnas.79.23.7440
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of bacteriophage T7 in vitro by incorporation of O6-methylguanine during DNA synthesis.

Abstract: An in vitro system in which bacteriophage T7 DNA is replicated and efficiently packaged into procapsids to form viable phage has been used to examine mutagenesis. The fidelity of replication was assayed both by measuring-reversion of an amber mutation in an essential gene and by generation of temperature-sensitive mutants among the phage produced in vitro. Under standard reaction conditions, the fidelity of DNA replication is about equal to that normally found in vivo. However, when O6_ methyldeoxyguanosine tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 27 publications
3
44
0
1
Order By: Relevance
“…The lower yield of phage found by using intact DNA and extracts from T7 3 Ϫ 5 Ϫ 6 Ϫ rather than from T7 3 Ϫ was not unexpected. Previous studies have shown that the absence of gene 6 reduces the ability of the packaging system to produce viable phage (4). This may be due to a role for the gene 6 product in maturation of the T7 genomes prior to packaging (28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower yield of phage found by using intact DNA and extracts from T7 3 Ϫ 5 Ϫ 6 Ϫ rather than from T7 3 Ϫ was not unexpected. Previous studies have shown that the absence of gene 6 reduces the ability of the packaging system to produce viable phage (4). This may be due to a role for the gene 6 product in maturation of the T7 genomes prior to packaging (28).…”
Section: Resultsmentioning
confidence: 99%
“…Our laboratory has been examining the repair of double-strand breaks by using an in vitro system based on extracts made from Escherichia coli infected with bacteriophage T7 (13,21,25,55). In this system, DNA replication closely mimics the in vivo replication of T7 DNA (4,28). Moreover, the in vitro system is able to carry out at least some steps of homologous recombination (22,23,27,38,39).…”
mentioning
confidence: 99%
“…Table 1 shows similar recovery of intact genomes whether uninfected extracts or no extract was used. The T7-infected extract gave a significantly higher yield of phage from the intact genomes, because of replication of the genomes during the reactions and because incubation in the T7-infected extracts improves the ability of the phage genomes to be packaged (6). A double strand break reduced yield of viable phage by 2 to 3 orders of magnitude if there was no extract in the reaction or uninfected E. coli was the source of extract.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the reaction of alkylating agents with the 06-atom of guanine fixes the enol tautomer of this base, in which guanine has been predicted to base-pair with thymine as well as cytosine (14). Much data from in vitro systems support this prediction (15)(16)(17)(18) (Fig. 1) (19).…”
Section: Introductionmentioning
confidence: 99%